Earth retention systems - Macnab, Alan (McGraw-Hill's AccessEngineering., 2002)
"An understanding of temporary excavation shoring and earth retention systems is essential for everyone in the construction and engineering community. Written by an industry expert with three decades' experience, this detailed handbook presents a systematic and comprehensive presentation of these complex systems." "Invaluable to firms involved in earth excavation, geotechnical and structural engineers, field supervisors, as well as safety officers, here is the definitive reference for anyone involved in the process of earth retention."--Jacket.